Results of Using Short Stories towards Learning Achievement on al-Hadith Subject for Primary School Students, Year 3 - อุเซ็ง อาอีเซ๊าะ (Al-HIKMAH Journal, 2021)
The purposes of this research were : 1) to construct and evaluate the efficiency of teachings and learning lesson plan of using short stories towards learning achievement on al-hadith subject for primary school students’ year 3. 2) to compare the students’ learning achievement who learned by using short stories towards learning achievement on al-hadith subject for primary school students, year 3 between before instruction instruction and after instruction. 3) to compare the students’ learning achievement by of using short stories towards learning achievement on al-hadith subject for primary school students, year 3. 19 people semester 2 academic year B.E. 2563 of ban thungriang school yopo distrit mueang district yala province . the research desigh quasi-experiment by using the pertest- posttest control design was employed to attain the students results the research’s instruments were. 1) lesson plans for instruction by using short stories and 5 lesson plans for instruction by using general learning. 2) learning Achievement’s test, 3) questionnaire form on Students’ satisfaction towards instruction by the both instruction. the data was analyzed by percentage, means standard deviation The results of the research were as follows : The efficiency of the lesson plans by using Short Stories for primary school students towards was 72.63/85.71, greater than 80/80 criteria preset. The students’ learning achievement who learned by using Short Stories after instruction was higher than before instruction which was considered statistically significant of 0.05 The students’ satisfaction towards instruction by using Short Stories was the hight.